Wisdom in loose form : the language of Egyptian and Greek proverbs in collections of the Hellenistic and Roman periods - Lazaridis, Nikolaos, 1977- (Mnemosyne, Supplements, 2007)
This book examines Ancient Egyptian and Greek proverbs, as they are found in wisdom collections, circulating in Egypt and Greece of the Hellenistic and Roman periods. Its examination compares the proverbs' grammar, structure, style, theme and usage within the collections. This multi-leveled comparison results in the indentification of a great number of similarities and differences that are interpreted in cultural terms, that is, through their association with the cultural context of production and usage of the proverbs. Hence this study offers an original insight into the literary production in Ancient Egypt and Greece, comparing the manner Egyptian and Greek authors conveyed timeless wisdom and reconsidering the status of cultural contact between these two ancient Mediterranean civilizations.